Students’ Perception of Class V in Endemic Era: A Case Study of One Private University in Jambi, Indonesia - Megawati, Merti; Soma, Robi; Akhyari, Azki; Sofyan, Sofyan; Kuntarto, Eko (PPSDP International Journal of Education, 2023)
The purpose of this qualitative study was to investigate and understand the students’ perception of Class V at one private university in Jambi. The qualitative method was used to carry out this study using semi-structured interview by asking questions to the participants in relation to what the students’ perceived about subjects presented using Class V in the endemic era. A semi-structure interview was employed as the technique of collecting the data. There were four participants who were willing to join the interview process. The findings of this study depicted that the role of Class V is very helpful for the students related to their assignment, presence, module and others helpful features. Through Class V the students feel easy to get the material, they could download the material or upload the assignment anytime and anywhere as they have already dealt it with the lecturer. The three salient themes appeared in this research were general perceptions about Class V, the role of Class V and problems of using Class V and the solution. As a part of Blended Learning system Class V is an alternative way for students in this endemic era.